Th22 cells are expanded in multiple sclerosis and are resistant to IFN-β. Issue 6 (5th August 2014) - Rolla, Simona; Bardina, Valentina; De Mercanti, Stefania; Quaglino, Pietro; De Palma, Raffaele; Gned, Dario; Brusa, Davide; Durelli, Luca; Novelli, Francesco; Clerico, Marinella
Abstract : Expansion of Th22 cells in multiple sclerosis could critically influence the resistance to IFN-β therapy. Abstract: Th1 and Th17 cells have been considered as effectors in mouse EAE and in the human counterpart, MS. Recently, IL-22, a Th17-related, proinflammatory cytokine, has been associated with a new Th cell subset, defined as Th22, involved in chronic inflammatory conditions, such as psoriasis; the role of IL-22 in MS has not yet been elucidated. Here, we report that similar to Th17 cells, the number of Th22 cells increased in the PB and the CSF of RR MS patients, especially during the active phases of the disease. However, as opposed to Th17 cells, the expansion of Th22 cells occurred before the active phases of the disease. Th22 cells were found to be specific for the autoantigen MBP and also expressed high levels of CCR6 and T-bet, as for Th17 cells, indicating that Th22 self-reactive cells could have CNS-homing properties and be pathogenic in active RRMS patients. Conversely to Th17 cells, Th22 cells displayed lower levels of IFNAR1 and were insensitive to IFN-β inhibition. These data suggest that expansion of Th22 cells in MS could be one of the factors that critically influence resistance to IFN-β therapy.